Structural and genetic analyses of the RdgC protein in Escherichia coli - Yu, Jing (2009)
Previous studies found that RdgC protein plays a role in the DNA repair system in Escherichia coli. In recBC sbcBC strains, loss of rdgC made growth of the strains dependent upon recombination, hence Recombination Dependent Growth. RdgC was also found to regulate the activity of RecA, a key protein in recombination, both in vivo and in vitro. The function of the protein, however, remains unknown.